Effect of constituent content on mechanical behaviors of ultra-high performance seawater sea-sand concrete. (10th October 2022) - Jiang, Kaidi; Wang, Xin; Chen, Zhiyuan; Ding, Lining; Peng, Zheqi; Wu, Zhishen
Highlights: The variation of mechanical behavior with sea shell contents was investigated. The preferable content of coarse aggregate for UHP-SSC matrix was 10% by volume. The utilization of basalt FRP minibars can enhance strength and toughness of UHP-SSC. Abstract: In this study, the mechanical behaviors of ultra-high performance seawater sea-sand concrete were investigated considering various constituent contents of sea shell (SH), coarse aggregate (CA), and basalt fiber reinforced polymer minibars (MB). Experimental results reveal that the mechanical strength first increased and then decreased as the SH content increased, which was attributed to the evolution of macroscopic pores. CA, which preferable content was 10%, hurt the workability and flexural strength of the matrix; in contrast, owing to its skeletal effect, the compressive strength increased at a small content of CA. Moreover, the utilization of the MB increased the compressive strength and flexural toughness and this enhancement is positively correlated with the increase in the minibar content.